South African Architectural Record - (:unkn) unknown (South African Architectural Institute, 1946)
South African Architectural Record
Journal of the Cape, Natal, Orange Free State and Transvaal Provincial Institutes of South African Architects and the Chapter of South African Quantity Surveyors.
Journals
Keywords: South African Architectural History